THE IMPORTANCE OF EARLY CHILDHOOD EDUCATION AND THE ROLE OF INFRASTRUCTURE FACILITIES IN SUPPORTING LEARNING IN ORCHID PLAY GROUPS (KOBER) IN KEDUNGJAYA VILLAGE, CIREBON - Winda Dwi Yanthi; Gian Fitralisma; M. Anissul Fata; Yeyet Daryati; Imas Trimayanti; Tornado Syukur; Tuty Syarifa Syahputri; Rachman Hidayat (Ann Publisher, 2025)
Abstract Background. Early childhood education (PAUD) is an essential foundation in child development. We compiled this study titled The Importance of Early Childhood Education and the Role of Infrastructure Facilities in Supporting Learning in Orchid Play Groups (Kober) in Kendungjaya Village, Cirebon. Aims. This study explores early childhood education's importance and infrastructure's role in supporting learning in the Orchid Play Group (Kober), Kedungjaya Village, Cirebon. Methods. The method used is qualitative research with a literature approach. The study results show that good education at an early age can improve children's cognitive, social, and emotional abilities. Conclusion. Adequate infrastructure also contributes significantly to learning effectiveness and children's growth and development. Implementation. Kober Orchid in Kedungjaya Village has shown that with the proper support, children can develop well. Therefore, all parties need to pay more attention to improving the quality of early childhood education. In addition, training for educators also needs to be improved so that they can provide quality education.